2013
DOI: 10.1021/es4030244
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Shallow Geothermal Energy Production on Redox Processes and Microbial Communities

Abstract: Shallow geothermal systems are increasingly being used to store or harvest thermal energy for heating or cooling purposes. This technology causes temperature perturbations exceeding the natural variations in aquifers, which may impact groundwater quality. Here, we report the results of laboratory experiments on the effect of temperature variations (5-80 °C) on redox processes and associated microbial communities in anoxic unconsolidated subsurface sediments. Both hydrochemical and microbiological data showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 72 publications
0
62
1
1
Order By: Relevance
“…In addition, sulfate reduction can cause anaerobic corrosion of ferrous metals, and to a lesser degree stainless steel, thereby reducing the lifespan of the thermal storage system [10]. In recent studies of the effects of aquifer thermal storage, Jesußek et al [1] and Bonte et al [10] reported a shift from iron reduction to sulfate reduction at 70 °C and 25 °C respectively.…”
Section: Ch Coo + So + H → 2hco + H S Aqmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, sulfate reduction can cause anaerobic corrosion of ferrous metals, and to a lesser degree stainless steel, thereby reducing the lifespan of the thermal storage system [10]. In recent studies of the effects of aquifer thermal storage, Jesußek et al [1] and Bonte et al [10] reported a shift from iron reduction to sulfate reduction at 70 °C and 25 °C respectively.…”
Section: Ch Coo + So + H → 2hco + H S Aqmentioning
confidence: 99%
“…In recent studies of the effects of aquifer thermal storage, Jesußek et al [1] and Bonte et al [10] reported a shift from iron reduction to sulfate reduction at 70 °C and 25 °C respectively. Both studies employed laboratory experiments.…”
Section: Ch Coo + So + H → 2hco + H S Aqmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent elementrelease patterns were only partially observed, e.g., for silicium and potassium. Adaptations of the microbial communities to temperature changes in both composition and quantity were found in field-monitoring campaigns (Vetter et al 2012;Würdemann et al 2014) and in the laboratory (Bonte et al 2013b).…”
mentioning
confidence: 96%